Pelletizing properties of raw and torrified Empty Fruit Bunches (EFB) - Wan Nur Khairunnisa Wan Jusoh (2017)
This study research focused on the properties of raw and torrified pellet from EFB by varying different parameters, including energy consumption, moisture adsorption, meyer hardness test and pellet density. To save storage space and transport costs, it can be compressed into fuel pellets of high physical and energetic density. The pelletizing properties were determined using single pellet press and pellet stability was determined by compression testing. Pelletization of raw and torrified empty fruit bunch (EFB) from compression single pellet press (SPP) was investigated to quantify the energy consumption and pellet properties, including moisture adsorption, pellet density and Meyer hardness . Energy consumption for torrified EFB pellet were significantly higher than those for raw EFB pellet, while the moisture adsorption rate of torrified EFB pellets increased with increasing the severity of torrefaction. Decomposition of hemicellulose and lignin reduced the plasticity of raw sample contributes to increase energy consumption during compression. The hardness of pellet made at same pelleting condition decreased with the increasing of size of sample. The densities of torrified EFB pellets were higher than raw EFB pellet due to the loss of chemically bonded water and low melting point compounds during torrefaction which act as binding agent. The properties of pellets were affected by the removal of most low melting or softening point components.